Adapting an IP MC6805 core for multiprocessing and multitasking - Jaquenod, Guillermo A. (2003)
The availability of high-density field configurable devices provides the opportunity for designing highly integrated solutions (SOPC: System On a Programmable Chip).\nAmong the SOPC solutions, a case is the integration of an embedded single processor equipped with a multitasking operating system. As an alternative to a single processor the embedding of various processors on a chip, even heterogeneous and with multitasking capacity, may be considered.\nA distinctive characteristic of a SOPC device is that the tasks to be performed are well known before the design starts. That feature is opposed to the traditional multiprocessing and multitasking systems in which general purpose applications are adopted during design. The benefit of this knowledge is that hardware as well as software can be adapted to fit the application’s requirements.\nThis paper presents the hardware modifications performed on an microcontroller embedded core, to allow its inclusion as a multitasking device in a “multiprocessor on a chip”, through the addition of a hardware task manager (scheduler) and communication channels among processors.